2017
DOI: 10.1007/s00520-017-3738-0
|View full text |Cite
|
Sign up to set email alerts
|

Low-level laser and antimicrobial photodynamic therapy on experimental periodontitis in rats submitted to chemotherapy by 5-fluorouracil

Abstract: LLLT and aPDT adjuvant to SRP minimized the effects of 5-FU on periodontal disease. Furthermore, aPDT promoted greater benefits in bone loss control and inflammatory response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 36 publications
1
15
0
Order By: Relevance
“…Even aggravation of EP in animals receiving 5‐FU had already been shown (Garcia et al., ; Theodoro et al., , ), the capacity of both CIS and 5‐FU to alter hosts’ immune and inflammatory response leading to bone loss in the initial periods of 3 and 5 days was firstly assessed by the present study. Additional studies are needed to better understand the effects and mechanisms of action of 5‐FU and CIS on periodontal tissues.…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…Even aggravation of EP in animals receiving 5‐FU had already been shown (Garcia et al., ; Theodoro et al., , ), the capacity of both CIS and 5‐FU to alter hosts’ immune and inflammatory response leading to bone loss in the initial periods of 3 and 5 days was firstly assessed by the present study. Additional studies are needed to better understand the effects and mechanisms of action of 5‐FU and CIS on periodontal tissues.…”
Section: Discussionmentioning
confidence: 56%
“…() and Theodoro et al. (, ). They concluded that 5‐FU exacerbated the inflammatory response and increased the severity of EP at 14, 22 and 37 days after its induction in rats.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…The findings of this animal experiment infer that implants inserted before chemotherapy are likely to be harmed by the treatment. As chemotherapy increases severity and accelerates the progression of experimental periodontitis (Garcia et al., ; Theodoro et al., ), clinically, exposure of these implants to plaque can lead to impairment of osseointegration due to severe peri‐implantitis. As CIS develops hazardous effect over bone repair and bone formation (Stine et al., , ), more studies are needed for proper and secure rehabilitation of patients previously submitted to chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies shown a high prevalence of periodontal diseases in patients receiving life-long immunosuppressive therapy [13][14][15] along with increases in plaque, bleeding, and gingival indices [16,17] and probing depth [18]. Indeed, studies in animals treated with chemotherapy have reported destruction and disorganization of all periodontal tissues, with the presence of large spicules of necrotic bone and intense inflammatory infiltrate, with a significant increase of alveolar bone loss in the furcation region [6,7,[19][20][21]. 5-Fluorouracil (5-FU) is a drug widely used in the treatment of carcinomas [22], is an analogue of the pyrimidine base uracil.…”
Section: Introductionmentioning
confidence: 99%